Does the New National Cervical Screening Programme Guideline Detect Cases of High-Grade Squamous Intraepithelial Lesions That Previously Would Have Been Missed? - Pontré, Jennifer C; Nathan, Elizabeth; Goldsmith, Hilary; McElhinney, Bernadette (Journal of lower genital tract disease, 2023)
The aim of this study was to determine the number of patients undergoing large loop excision of the transformation zone (LLETZ), for biopsy-confirmed high-grade squamous intraepithelial lesions (HSIL), where the original cervical screening test (CST) reported oncogenic human papillomavirus (HPV) and negative liquid-based cytology (LBC). This reflects the number of patients where a LLETZ procedure would not have occurred under the previous guideline. Retrospective observational chart review of all patients (n = 477) who underwent LLETZ procedure in a single tertiary unit over a 36-month period. Prevalence of negative histopathology, positive margins, incidental cervical cancer, and accuracy of HSIL identification at colposcopy were measured. Diagnostic accuracy of HSIL diagnosis from initial colposcopic impression was calculated; factors influencing accuracy were evaluated using multivariable logistic regression analysis. There were no comparators. Of 477 LLETZs, 5.9% (n = 28) were for oncogenic HPV and normal LBC on referral CST. Demographics between the "study" (oncogenic HPV and normal LBC on referral CST) and the "standard" group were similar, except the study group was less likely to be using contraception (25% vs 47%, p = .023). In the study group, initial colposcopic cervical biopsy confirmed HSIL in 91.6% (n = 27) and low-grade squamous intraepithelial lesions in 3.6% (n = 1). Histopathological analysis of LLETZ specimens confirmed HSIL in 20 patients (71.4%) and low-grade squamous intraepithelial lesions in 2 (7.1%). No microinvasion was detected. The renewed National Cervical Screening Programme (NCSP), is detecting more "at risk" patients, predicted to lead to a further reduction in incidence of cervical cancer in adequately screened patients.